1977
DOI: 10.1002/art.1780200116
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing polychondritis

Abstract: Ear cartilage from a typical case of relapsing polychondritis was examined with the electron microscope. A large number of dense granules and vesicles, which were compatible with matrix vesicles or lysosomes, surrounded the affected chondrocytes. In less severely damaged chondrocytes, these granules and vesicles appeared to be formed by pinching off of the cytoplasmic processes or by budding from the processes. Calcification of the granules was minimal. In severely damaged chondrocytes, an admixture of these g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In an electron microscopic analysis of auricular chondritis, degenerating chondrocytes released matrix vesicles (7). It was suggested that some of the matrix vesicles | 637 contained proteolytic enzymes and were functionally similar to lysosomes (7). It is conceivable that accelerated immune responses are involved in the chondrocyte degeneration in patients with RP (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an electron microscopic analysis of auricular chondritis, degenerating chondrocytes released matrix vesicles (7). It was suggested that some of the matrix vesicles | 637 contained proteolytic enzymes and were functionally similar to lysosomes (7). It is conceivable that accelerated immune responses are involved in the chondrocyte degeneration in patients with RP (8).…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase-3 (MMP3) was produced by activated chondrocytes in the RP lesions, and the expressing cell numbers positively correlated with apoptotic chondrocyte numbers (6). In an electron microscopic analysis of auricular chondritis, degenerating chondrocytes released matrix vesicles (7). It was suggested that some of the matrix vesicles | 637 contained proteolytic enzymes and were functionally similar to lysosomes (7).…”
Section: Introductionmentioning
confidence: 99%